Cognition-Sociocultural in Tempo Newspaper Article entitled “Evaluasi Pemilu Serentak Mendesak” - Rendy Pribadi; Yasir Riady (LADU: Journal of Languages and Education, 2022)
Background: There was a different technique when the Critical Discourse Analysis (CDA) framework came into effect, from elements, Fairclough analysis frameworks that explained the historical side of text production to the impact on society and the framework of CDA van Dijk that characterized the cognition of the producer of the text (journalist). Purpose: This study tries to find elements of cognition and sociocultural from the article Evaluation of Evaluasi Pemilu Serentak Mendesak from Tempo newspaper with the framework model of CDA Fairclough and van Dijk model. Design and methods: This research uses a qualitative approach with data collection methods using library methods. Content analysis techniques. Results: The authors found several techniques in dissecting the text; 1. CDA Fairclough model focuses more on changes in social patterns, 2. Social cognition only reads events and conveys them to the reader so that the responsibility is centered on journalists.